Alteration of gut microbiota during narrowband ultraviolet B therapy in psoriasis: A preliminary study. Issue 8 (29th June 2022) - Rungjang, Atiya; Meephansan, Jitlada; Payungporn, Sunchai; Sawaswong, Vorthon; Chanchaem, Prangwalai; Pureesrisak, Purit; Wongpiyabovorn, Jongkonnee; Thio, Hok Bing
Abstract: Gut microbiome dysbiosis is associated with psoriasis development. A relationship between gut microbiota and psoriasis treatment response has been reported. No study has reported the effect of narrowband ultraviolet B (NBUVB) therapy, a standard treatment of psoriasis, on gut microbiota. This study aimed to evaluate gut microbiota change during NBUVB therapy. Stool samples from 22 participants, including 13 patients with chronic plaque psoriasis and nine healthy controls, were recruited. Faecal microbiota composition was analysed using 16S rRNA sequencing before and after NBUVB therapy. Serum 25‐OH vitamin D of patients with psoriasis was evaluated simultaneously. The most abundant phyla of gut microbiota in patients with psoriasis were Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria in all participants. Bilophila, Paraprevotella, Alistipes, Sutterella, Romboutsia, Clostridium sensu stricto and Agathobacter are significantly more enriched in healthy controls. Lactobacillales and Ruminococus torques appeared more enriched after NBUVB treatment in responders but not non‐responders. Serum vitamin D levels significantly increased after NBUVB treatment. The present study revealed that gut microbiota altered after NBUVB treatment. The change might be treatment‐specific and influence the treatment response.